IMPROVEMENT OF THE “VOLODINNA” CONSTRUCT IN THE STRUCTURE OF SPECIFICITY TYPICAL TO THE METHOD OF PSYCHOTHERAPY “I-RECONSTRUCTION” - Pavlenko, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyzes the concept of the structure of specialness in the method of psychotherapy “I-reconstruction”, and defines the important concept of “possession” as one of the main warehouses. The author's design has been dismantled. Theoretical materials are illustrated with the following tables. There is further research in the emerging views on the role of the construct “possession” in the formation of injuries and their influx into life. Research methods: theoretical analysis, scientific research in psychology, medicine; systematization and logical organization of the extracted material. The follow-up procedure transferred the findings of the bibliographical, step-by-step problem-based and step-by-step methods using the method of understanding the construct “possession” in the structure of the particularity similar to the method of psychotherapy “I-reconstruction” (Pavlenko, 2022). It has been shown that in order to develop the structure of a particularity, it is necessary to maintain low criteria of similarity in order to allow internal processes to be modified in the new world. In our case, the main constructs are nutritiousness, volition and satisfaction. In this article, a completely new look was proposed at the role of fluid in the life of the individual, which was infused with other structural elements in the human psyche. As a result, the author’s designation of the construct “possession” was established, and the formation of trauma to this construct was illustrated in accordance with the method of psychotherapy “I-reconstruction”. In this work, the role of the construct “possession” in the structure of specialness was established, and the ability to work in it, in the psychotherapeutic process, was shown. For example, problems in food behavior, the development of delay in speeches, drugs and people, throwing out food or giving away your speeches, a tendency to impulsive purchases are signs of injury to this construct